Shortage of water in Teesta river basin and its impact on crop production in northern Bangladesh - Raihan, ML; Sarker, MA; Miah, MAM (SAARC Journal of Agriculture, 2018)
The objectives of the study were to (i) assess the extent of water shortage in the downstream of Teesta River Basin (TRB) areas; (ii) explore the problems associated with crop production due to water shortage in TRB areas and (iii) examine the impact of water shortage on crop production in TRB areas. The study was conducted in four villages under Nilphmari district during April, 2015. By secondary data analysis and farmers’ perception it was clear that water flow and discharge of Teesta river was decreasing significantly during the last 15 years. The major impact was the dramatic increase in costs of irrigation of major crops and ultimately rise in the costs of production and less profit from farming. All of the farmers (100%) opined that the irrigation costs of major crops have been increasing due to shortage of water. The cultivation of LWRC due to water shortage was also a major impact of water shortage on crop production. Farmers were concentrating more on cultivating maize, tobacco, wheat, different types of vegetables etc. compared to rice particularly in dry season. Different types of problems like increased amount of heavy metal in crop land due to continuous uplifting of ground water, decrease soil fertility, increase pests and diseases to crops, fallowing of high and medium high land, increase of fertilizer and pesticide costs etc. were affecting farmers severely in crop production. SAARC J. Agri., 15(2): 113-123 (2017)